Miskonsepsi Materi KPK dan FPB Berdasarkan Gender - Gita Cahyani; Ulum Fatmahanik (Indonesian Mathematics Education Journal, 2024)
Misconceptions are something that often happens to students, this must be overcome because if misconceptions are allowed to continue, they can hinder student learning success. Misconceptions occur in many students throughout Indonesia, both male and female, due to the students themselves, the teacher, the text, the context and the way of teaching. Misconceptions also occur at MI Kanzul Huda due to the students themselves, teachers and teaching methods. So that in this study will be discussed related to misconceptions using CRI. The aims of this study were to 1) describe students' misconceptions in learning mathematics on KPK and FPB materials using CRI based on gender, 2) describe the causes of student misconceptions and 3) find out the efforts to overcome student misconceptions. The approach in this study is a descriptive qualitative approach. Determination of subjects is determined based on gender with criteria based on the highest achievement and having good communication. Data collection techniques used CRI-based tests and interviews, the instruments used misconception test sheets in the form of essay questions and used the CRI misconception measuring tool. The results showed that male subjects were more likely to experience misconceptions than female subjects. Of the 6 subjects taken, namely 3 men and 3 women, all male subjects.